Pengaruh Penggunaan Jenis Desikan dan Penyimpanan terhadap Viabilitas dan Vigor Benih Kedelai (Glycine max L. Merr.) Kultivar Anjasmoro - Irwan, A.W.; Sunarto, T.; Wahyudin, A. (Jurnal Agroteknologi (Agronu), 2024)
Conditions for good seed storage are part of a series of seed production and storage methods that affect the storability and quality of seeds. The use of desiccants can increase the viability and vigor of seeds in storage. This study aims to determine the right type of desiccant for soybean seed storage at various storage times. The research was carried out from February to July 2024 in Rancaekek Kencana Village, Bandung Regency with an altitude of about 700 meters above sea level. The study used a factorial completely randomized design (CRD) with four replications. The first factor is the type of desiccant consisting of three kinds, namely sawdust, activated carbon and silica gel. The second factor is storage time consisting of four levels, namely 4,8,12, and 16 weeks. The results showed that there was an interaction between the type of desiccant and storage time on water content and seed weight after storage. The germination capacity of soybean seeds showed no influence on various types of desiccants (sawdust, activated carbon and silica gel), namely between 87.25% - 94.75%, while the storage time of 8 weeks did not show any difference with the storage time of 4 weeks, which was 92.12%